2020
DOI: 10.3390/genes11091092
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Differences between Subcutaneous and Visceral Adipocytes Differentiated with an Excess of Saturated and Monounsaturated Fatty Acids

Abstract: Obesity is a major health problem in highly industrialized countries. High-fat diet (HFD) is one of the most common causes of obesity and obesity-related disorders. There are considerable differences between fat depots and the corresponding risks of metabolic disorders. We investigated the various effects of an excess of fatty acids (palmitic 16:0, stearic 18:0, and oleic acids 18:1n−9) on adipogenesis of subcutaneous- and visceral-derived mesenchymal stem cells (MSCs) and phenotypes of mature adipocytes. MSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Visceral adipose tissue is more susceptible to reduction compared to subcutaneous adipose tissue because adipocytes of the epiploic and mesenteric adipose tissue, the main components of visceral fat, show greater metabolic activity and lipolytic sensitivity [ 41 43 ]. Subcutaneous and visceral adipocytes show differences in the expression of certain genes [ 44 ]; visceral adipocytes are characterised by higher lipolytic activity (significantly higher expression of the lipoprotein lipase gene) than subcutaneous adipocytes [ 45 ]. This may be important for fat mobilisation during lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Visceral adipose tissue is more susceptible to reduction compared to subcutaneous adipose tissue because adipocytes of the epiploic and mesenteric adipose tissue, the main components of visceral fat, show greater metabolic activity and lipolytic sensitivity [ 41 43 ]. Subcutaneous and visceral adipocytes show differences in the expression of certain genes [ 44 ]; visceral adipocytes are characterised by higher lipolytic activity (significantly higher expression of the lipoprotein lipase gene) than subcutaneous adipocytes [ 45 ]. This may be important for fat mobilisation during lactation.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that SAT and VAT fat depot differ significantly, especially according to the risk of metabolic disorder developments. Probably due to higher inflammatory markers in VAT, this type of tissue has been associated with a higher risk of metabolic disorder pathogenesis [19]. The 3T3-L1 adipocytes revealed expression similar to SAT adipocytes; the reduction was seen only at the second time point, which means that this type of cell is more similar to the SAT depot and does not correspond to the VAT depot.…”
Section: Discussionmentioning
confidence: 99%
“…Primers were designed manually and the efficiency of primers was checked by a standard curve. The sequence of primers was published previously [11,19]. Normalization was executed on the housekeeping gene (β-actin) and calculated according to the ∆∆Ct algorithm.…”
Section: Gene Expressionmentioning
confidence: 99%
“…The process of preadipocyte differentiation into mature adipocytes has previously been optimized and published [ 19 , 20 ]. The progress of the adipogenesis process was controlled by lipids accumulation measurement and morphological changes.…”
Section: Methodsmentioning
confidence: 99%